PENGARUH RELAKSASI LIMA JARI TERHADAP DEPRESI PADA - I Nengah sumirta (Jurnal Gema Keperawatan, 2018)
The purpose of this study was to knowing the influence of five finger relaxation of depression to People With HIV / AIDS (PLWHA) at Spirit Paramacitta Foundation, Denpasar. This study used pre-experimental design with a pretest-posttest group design. The sample used is 18 people selected by purposive sampling technique. The results showed that the category of depression before relaxation mostly in the moderate depression as many as  13 people (72.2%), and after relaxation showed that a decrease in the number of moderate depression to be 9 people (50.0%). The results of this study were tested by paired-sample t-test statistic, the results obtained value (р) = 0.012 (p 0.05) it can be concluded that there is effect of five-finger relaxation to depression in people living with HIV / AIDS ) at Spirit Paramacitta Foundation, Denpasar Year 2018.